2021
DOI: 10.1108/bij-10-2020-0528
|View full text |Cite
|
Sign up to set email alerts
|

Electronic customer relationship management (E-CRM), customer experience and customer satisfaction: evidence from the banking industry

Abstract: PurposeThe purpose of this paper was to examine the relationship between electronic customer relationship management (E-CRM) and customer satisfaction through the mediating role of customer experience in the banking industry.Design/methodology/approachThe data were collected from customers of 10 banks (5 public and 5 private sector banks) of Delhi, India. In total, 836 useable structured questionnaires were filled, and the data were analyzed using structural equation modeling (SEM) through AMOS.FindingsThe res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 70 publications
4
50
0
1
Order By: Relevance
“…Therefore, companies must fully understand the importance of meeting customer needs and going beyond their product or service quality expectations. Because customer satisfaction and ultimately increasing the chances of companies retaining them is very important because the cost of retaining existing customers is less than the cost of attracting new customers (Kumar et al, 2021Wangwacharakul et al, 2021, it is widely accepted in the literature that loyalty is based on satisfaction (Byon, 2020;Núñez-Barriopedro et al, 2021). Thus, we hypothesise: H4.…”
Section: Customer Satisfactionmentioning
confidence: 95%
“…Therefore, companies must fully understand the importance of meeting customer needs and going beyond their product or service quality expectations. Because customer satisfaction and ultimately increasing the chances of companies retaining them is very important because the cost of retaining existing customers is less than the cost of attracting new customers (Kumar et al, 2021Wangwacharakul et al, 2021, it is widely accepted in the literature that loyalty is based on satisfaction (Byon, 2020;Núñez-Barriopedro et al, 2021). Thus, we hypothesise: H4.…”
Section: Customer Satisfactionmentioning
confidence: 95%
“…On the other hand, when the quality of a product sold by the company was deemed as "good" or even "perfect" by its customers, they have a tendency to re-buy the product from the company. Based on the literature above, companies should thoroughly understand the importance of satisfying customers needs and exceeding their expectations regarding the quality of a product or service, in order to increase the company's chance of satisfying them and ultimately increase the chance of retaining them, since the cost of retaining existing customers is lower than the cost needed to recruit new customers (Lam and Burton, 2006;Juliana et al, 2021;Kumar et al, 2021;Wangwacharakul et al, 2021).…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Thus, proper implementation of E-CRM services leads to customer satisfaction. Though, the previous literature pointed out the positive relationship between E-CRM and customer satisfaction (Al-Dmour et al, 2019;Ismail & Hussin 2016;Kaur, 2016;Kumar et al, 2021;Mang'unyi et al, 2018;Mulyono & Situmorang, 2018;Oumar et al, 2017;Rashwan et al, 2019;Upadhyaya, 2020), the study proposed by Tariq et al, (2019) revealed that there is no such relationship exists between E-CRM and customer satisfaction rather it decreases satisfaction level. Hence, there is a need to study the relationship between E-CRM and customer satisfaction.…”
Section: E-crm and Customer Satisfactionmentioning
confidence: 95%